"Vocabularius breviloquus" Johannesa Reuchlina jako podstawa rękopiśmiennego Słownika Bartłomieja z Bydgoszczy (na materiale nazw własnych) - Lenartowicz-Zagrodna, Anna; Trawińska, Maria (Collectanea Philologica, 2024)
One of he copies of the dictionary entitled Vocabularius breviloquus, compiled by Johannes Reuchlin, became the property of Bartłomiej of Bydgoszcz. This Polish monk added handwritten annotations in Polish or Latin in the margins of the old print, with his comments being selective, focusing on chosen Latin entries or their parts. Currently, as part of a project, work is underway on the Latin-Polish edition of the dictionary. An editorial challenge lies in presenting the Latin base, i.e., the entries prepared by Reuchlin. An analysis of proper names reveals how the German lexicographer constructed entry articles (what information he included) and how Bartłomiej processed them. The analysis indicates further that Bartłomiej did not include all entries related to proper names, significantly modifying (shortening) the remaining ones. Additionally, he independently added some entries not present in Vocabularius, thereby expanding the lexical base.